Significance of HbA1c in Diagnosing and Prognosing Diabetes Related Complications (Journal of Rangpur Medical College, 2025)
Background: Diabetes mellitus, characterized by chronic hyperglycemia, results in serious complications. The HbA1c assay plays a central role in the diagnosis and monitoring of diabetes. Objective: To evaluate the contribution of HbA1c in the diagnosis and prediction of diabetes complications. Methods: The cohort was conducted at Sir Salimullah Medical College, Dhaka, Bangladeshfrom July 1, 2017, to July 30, 2018, over 96 diabetic patients aged more than 18 years to determine the importance of the HbA1c for diagnosing and predicting diabetic complications such as retinopathy, nephropathy, neuropathy, and cardiovascular complications. HbA1c by HPLC, fasting blood glucose (FBG), postprandial blood glucose (PPBG), lipid profile, and renal/liver tests were conducted every three months for one year.For determining correlation and relation, correlation and regression analysis were done. Results: Average HbA1c was 8.2±1.4%, indicating poor glycemic control. HbA1c correlated strongly with FBG (r=0.72) and PPBG (r=0.68). Complications included retinopathy (15.6%), nephropathy (20.8%), neuropathy (26%), and cardiovascular events (18.7%). Increased HbA1c was linked to an increased risk of complications (HR 1.45, 95% CI: 1.20-1.75, p